The Use of Academic Words amongst Sanata Dharma Univeristy’s ELESP Students Batch 2020 - Luig, Chiara Puspa; Ena, F.X Ouda Teda (Talenta Publisher, 2024)
Understanding how to use academic words is crucial and essential for university students. This is intended so that students can communicate their thoughts effectively by utilizing accurate academic words that fit the context. However, analyzing written work can be one technique to measure students’ proficiency with academic words. In this article, the author goes over percentages as well as examples of how academic words have been used in an academic writing by the students of the English Language Education Study Program (ELESP) by using a software called AntWordProfiller as a vocabulary profiler tool for this corpus-based analysis study. The study's findings indicated that on average, students’ academic writing covered 10% of the total AWL, which means that the academic writing have employed a good amount of academic words. This research also adds to the understanding of how non-native English language learners use academic words in their academic writing.